(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2009)
The thermochemical properties of melts of binary systems Si – Dy(Ho, Er) and three-component systems Si – Al – Dy(Ho, Er) along one – two cuts for each system at 1880 ± 10 К are studied by the method of a calorimetry in the isothermal hyperthermal calorimeter. Established, that all studied alloys will be derivated with allocation of a significant amount of a heat. In all an interval of structures the thermochemical properties are counted from the data for double boundary systems on equations Bonnier-Cabo, Tup, Colier.